1994
DOI: 10.1006/cgip.1994.1012
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Ellipsoids from Projections

Abstract: In this paper we examine the problem of reconstructing a (possibly dynamic) ellipsoid from its (possibly inconsistent) orthogonal silhouette projections. We present a particularly convenient representation of ellipsoids as elements of the vector space of symmetric matrices. The relationship between an ellipsoid and its orthogonal projections in this representation is linear, unlike the standard parameterization based on semi-axis length and orientation. This representation is used to completely and simply char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In Section 3.1.1 , it was shown that there exists a direct relation between the lengths of the principal axes of an ellipse and the covariance matrix of the pixel coordinates. In [ 30 ], it is shown how to obtain the variances of the ellipsoid projections using its own variances.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Section 3.1.1 , it was shown that there exists a direct relation between the lengths of the principal axes of an ellipse and the covariance matrix of the pixel coordinates. In [ 30 ], it is shown how to obtain the variances of the ellipsoid projections using its own variances.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Examples of fruits that approximate these shapes are also shown in Figure 6. An interesting property of ellipsoids, and spheroids in particular, is that the shapes of their orthogonal projections are ellipses [30]. Given the size of the fruits and the typical height of the camera (about 1 m), perspective effects are negligible and a parallel camera can be assumed locally for each fruit [31].…”
Section: Modeling the 3d Shape Of The Fruitsmentioning
confidence: 99%
“…Computation methods for the evaluation of the cross-section of the ellipsoid have been studied by other authors. 8,9 For completeness, the the main points of these calculations are summarized here. A 3D ellipsoid centered at the origin is given by…”
Section: Cross-sectional Ellipsementioning
confidence: 99%
“…Mathematically we seek a vector to satisfy the following equation (4) III. PARAMETERIZATION OF GEOMETRY Many shape parameterization options are available in literature such as Fourier descriptors [25], Lagrange interpolation [26] and parametrically defined shapes [27], [28] based on global representation of the geometry, as well as B-splines [29]- [31] where the control points determine the properties of the curve. We choose B-splines to model the irregular transition layer between adipose and fibroglandular layers where the control points determine the shape of boundary.…”
Section: Problem Statementmentioning
confidence: 99%